Roving bandits in action: Outside option and governmental predation in autocracies - Alexander Libman; Vladimir Kozlov; André Schultz (Frankfurt School of Finance & Management, 2012)
The paper investigates the influence of outside options on the predatory behavior of autocrats. An outside option is referred to as the opportunity of an incumbent ruler to continue his career outside his current territory of control. The paper uses data on the effectiveness of tax collection and the repressiveness of tax jurisprudence for Russian regions in 2007-2009 and finds that regions ruled by governors with substantial outside options are characterized by more repressive behavior of tax authorities. However, surprisingly, the same tax authorities collect less additional revenues for the public budget. It conjectures that the presence of an outside option induces autocrats to behave like roving bandits they use tax audits to establish control over regional companies, but exploit this control to extract private rents rather than revenues for the regional budget used for public goods provision.
Keywords: D72; D73; H77; P26; 330; roving and stationary bandit; tax auditing; predatory government; Russian federalism; Finanzverwaltung; Regionalverwaltung; Autoritäres System; Steuerliche Betriebsprüfung; Rent Seeking; Russland